Resonant diffraction radiation from inclined gratings and bunchlength measurements - Potylitsyn A. P. Alexander Petrovich (2008, 2008)
A simple scheme for the measurement of sub-mm bunch lengths using coherent resonant diffraction radiation (CRDR) from a tiltedgrating is proposed. The CRDR spectral-angular characteristics have been calculated using an adapted Kirchhoff model, taking intoaccount the pre-wave zone effect. It is shown that the latter leads to a distortion of the CRDR monochromaticity. Choosing the appropriatedistance between grating and detector such that the pre-wave zone effect becomes negligible, it is possible to measure the CRDRyield in the sub-THz range by a broadband detector. While changing the grating inclination angle with respect to the beam axis, theCRDR line is shifted and it is possible to obtain information about the bunch length, measuring the signal ratio from two detectorslocated at fixed observation angles instead of complicated spectral measurements which rely on absolute values of the intensity.